The Role of Computed Tomography (CT) Scan in Assessment of the Parametrial Involvement in Early Stage Cervical Carcinoma - Mohamad Nasir Shafiee,; Nazimah Idris,; Rushdan Mohd Noor, (Department of Surgery, UKM Medical Centre, 2012)
This retrospective study is aimed at evaluating the role of CT scan in predicting parametrium involvement in early stage of cervical carcinoma. It was conducted in a Gynaecologic Oncology Centre, Hospital Alor Star from January 2004 till December 2008. All patients with operable stage I and II cervical cancer had pelvic CT scan for evaluation of parametrium involvement before undergoing radical hysterectomy and pelvic lymphadenectomy. Parametrial streakiness or presence of infiltration suggested local invasion. Following radical hysterectomy, the specimens sent for histological confirmation and the correlation between the CT scan finding and the histopathology result was studied. The result revealed a total of 104 patients with operable stage cervical carcinoma had pelvic CT scan. The sensitivity and the specificity of CT scan in assessing parametrial involvement was 33.3% and 84.8%, respectively. In conclusion, CT scan had high specificity but low sensitivity in determining parametrial involvement in early stage of cervical cancer. Hence, routine preoperative pelvic CT scan has a limited role in assessing parametrial involvement in early stage cervical carcinoma.